Management of Retinal Detachment Associated with Morning Glory Disc Syndrome - Etheridge, Tyler (Case Rep Ophthalmol, 2021)
We report a case of morning glory disc anomaly in a young patient with tractional retinal detachment successfully repaired with complex pars plana vitrectomy, membrane peel, laser, and oil tamponade. A 19-year-old female with a history of right morning glory disc anomaly associated with PAX6 gene mutation presented with floaters, photopsia, central scotoma, and visual acuity (VA) of 1/200. A complex macula-involving tractional retinal detachment centered around the optic nerve with a morning glory disc anomaly. Retinal detachment was treated with 25-gauge pars plana vitrectomy with difficult separation of the posterior hyaloid. Fibrous preretinal membranes were peeled, a temporal relaxing retinotomy was required, subretinal fluid was drained through a superonasal retinotomy during air-fluid exchange, endolaser was applied, and tamponade was achieved with 1,000-centistoke silicone oil. The retina remained attached at 1-year follow-up, with VA count fingers throughout. Morning glory disc is a rare congenital anomaly associated with PAX6 gene mutation that most often occurs unilaterally. It is rarely associated with tractional retinal detachment. Optimization of visual outcome is imperative despite a poor visual prognosis.